Effect of air dielectric barrier discharge plasma treatment on the adhesion property of sanded polyphenylene sulfide. (August 2016) - Hong, Rui; Xu, Dongxia; Wang, Xiaojun; Long, Shengru; Zhang, Gang; Yang, Jie
Air dielectric barrier discharge (DBD) plasma was employed to treat the sanded polyphenylene sulfide (PPS) surface. The plasma-treated PPS samples were bonded with epoxy adhesive, and the adhesion strength was measured by the single lap-joint specimen test. Scanning electron microscopy (SEM), water contact angle analysis, and X-ray photoelectron spectroscopy (XPS) were applied to investigate the effect of the plasma treatment on the PPS surface property. A slight etching trace was detected after the plasma treatment according to the SEM images. XPS and water contact angle analysis indicated that the plasma treatment introduced sulfide oxides (S=O and O=S=O) onto the PPS surface leading to a higher surface energy. A steady improvement of bonding shear strength was achieved with the increase of plasma treatment time or discharge power density, which was consistent with the failure mode study. According to the above analysis, the air DBD plasma treatment could effectively improve the adhesion property of PPS.